Role of multilayer flow modulator stents in the treatment of arterial aneurysms - Rasit Dinc; Evren Ekingen (Therapeutic Advances in Cardiovascular Disease)
Arterial aneurysms remain a significant public health problem because they often result in death when ruptured; therefore, they require immediate medical treatment. Endovascular aneurysm repair (EVAR) has recently become the primary treatment option, owing to the fewer side effects compared to those with open surgery. However, stents used for conventional EVAR often cause side-branch occlusion, which alters the perfusion of vital organs. Recently, multilayer flow modulator (MFM) stents have been used as a new treatment for arterial aneurysms. These stents appear to be feasible owing to their unique design consisting of an uncoated three-dimensionally braided multilayered structure. MFM stents generally remodulate laminar flow and reduce the flow velocity in the aneurysmal sac, leading to thrombosis, which causes the aneurysm to shrink over time. Thus, they reduce the risk of mortality. Moreover, they reduce morbidity by preserving the side-branch blood flow. They can be easily applied to complex aneurysms and are ready to use without customization, which shortens the waiting time for interventions. This study aimed to evaluate the role of MFM stents in the treatment of arterial aneurysms based on available data.